Physiochemical Quality and Sensory Characteristics of koji Made with Soybean, Rice, and Wheat for Commercial doenjang Production - Hyun Hee Hong; Mina K. Kim (Foods, 2020)
The purpose of this study was to compare the physiochemical quality characteristics and sensory profiles of three types of koji: soybean, rice, and wheat koji. Koji is made by inoculating Aspergillus oryzae following the standard method of manufacturing. The physiochemical characteristic and sensory profiles were performed after fermenting samples of koji for a 72 h period. The physiochemical quality characteristics that were tested include pH, moisture content, color, acidity, TA, amino-type nitrogen content, reducing- and total-sugar content, and alcohol content; the enzymatic activities that were tested include amylase (α- and β-) and protease (neutral and acidic) activities. A descriptive sensory analysis was conducted on three types of koji with a highly trained sensory panel (n = 7) using the SpectrumTM Method. Differences in physiochemical and sensory profiles were observed on three koji samples (p < 0.05). Soybean koji had higher values in acid and TA, while rice koji had the highest values in reducing and total sugar, at 90.3 mg/g and 107.5 mg/g respectively. Wheat koji had the lowest values in protease activities. The flavor profile of soybean koji was characterized by bean sprout, cracker, and cheonggukjang aromatics; that of rice koji was characterized by overripe banana, solvent, syrup, and parboiled rice aromatics; and that of wheat koji was characterized by woody and roasted aromatics.